2017
DOI: 10.1177/0885328217712110
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic acid and Arg-Gly-Asp peptide modified Graphene oxide with dual receptor-targeting function for cancer therapy

Abstract: Graphene oxide (GO) modified with hyaluronic acid (HA) and Arg-gly-asp peptide (RGD) was designed as a dual-receptor targeting drug delivery system to enhance the specificity and efficiency of anticancer drug delivery. Firstly, GO-HA-RGD conjugate was characterized to reveal its structure and morphology. Whereafter, doxorubicin (Dox) as a model drug was loaded on GO-HA-RGD carrier, which displayed a high loading rate (72.9%, GO:Dox (w/w) = 1:1), pH-response and sustained drug release behavior. Cytotoxicity exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 59 publications
3
21
0
Order By: Relevance
“…This interaction regulates the expression of tumor-related proteins during carcinogenesis in patients with rectal and/or lung cancer [ 29 , 30 ]. Moreover, integrin interacts with HA to modulate differentiation and metastasis of tumor cells [ 31 , 32 ], suggesting a mechanism involving the stimulation of downstream effects upon OPN and integrin receptor interaction. This includes extracellular signaling and regulation of HA synthesis, thereby affecting the development of OA.…”
Section: Discussionmentioning
confidence: 99%
“…This interaction regulates the expression of tumor-related proteins during carcinogenesis in patients with rectal and/or lung cancer [ 29 , 30 ]. Moreover, integrin interacts with HA to modulate differentiation and metastasis of tumor cells [ 31 , 32 ], suggesting a mechanism involving the stimulation of downstream effects upon OPN and integrin receptor interaction. This includes extracellular signaling and regulation of HA synthesis, thereby affecting the development of OA.…”
Section: Discussionmentioning
confidence: 99%
“…Such modified forms of graphene can include materials such as iron oxide nanoparticles, polypyrrole, and silver nanoparticles, and the combination of these materials with graphene oxide can be induced to release more drug loaded onto them through the external application of stimuli such as magnetic fields, electricity, and near‐infrared light, respectively . Graphene can also be functionalized with a wide variety of materials that would allow for the specific targeting of cancer cells, including folic acid, antibodies, and RGD peptides . Such modifications can not only enable higher effective doses of drug delivered to cancer cells, but can also reduce the toxicity to surrounding healthy tissue caused by nonspecific delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Guo et al developed a dual-receptor-targeting drug delivery system, in which GO was functionalized with HA via ADH linker, and further with Arg–Gly–Asp peptide (RGD) for targeted drug delivery with more selectivity and specificity [ 156 ]. The synthesis first involves the modification of HA with ADH to introduce an amino group on the HA’s surface.…”
Section: Graphene Oxide Nanoparticles: Synthesis Unique Propertiementioning
confidence: 99%
“…Cellular uptake study revealed higher cellular uptake of GO–HA–RGD–DOX compared to GO–HA–DOX or GO–DOX systems. This specific dual targeting ability was achieved through the combined effect of the CD44–HA receptor, and integrin–RGD-facilitated endocytosis [ 156 ].…”
Section: Graphene Oxide Nanoparticles: Synthesis Unique Propertiementioning
confidence: 99%